Empathy: A challenge for the new generations of dentistry students at the University of Buenos Aires - Pastorino, Patricia (2025)
Empathy is the ability to be aware of and understand the emotions, feelings and ideas of others. Assessing empathy levels among dental students is essential for improving educational strategies and patient outcomes. Aim: The aim of this study was to assess the levels of empathy among dental students at the University of Buenos Aires (UBA) and analyze differences based on academic year and gender. Materials and Method: The study involved third- to sixth-year dental students at UBA. Participants provided informed consent and completed a sociodemographic questionnaire: the Jefferson Scale of Empathy – Health Care Provider Student version (JSE-HPS). Data analysis included descriptive statistics, t-tests for gender and academic year differences, and assessment of empathy dimensions. Results: Among 424 participants, the average JSE-HPS score was 108.2 (SD = 15.0), ranging from 36 to 134. The dimension of emotional and compassionate care had a mean of 35.7 (SD = 5.5), perspective taking had a mean of 59.0 (SD = 9.7) and standing in the patient’s shoes had a mean of 13.4 (SD = 3.6). Empathy scores increased from the third year (100.9, SD = 22.4) to the fifth year (111.5, SD = 10.0), with a slight drop in the sixth year (110.6, SD = 12). Females (mean 109.0, SD = 15.5) displayed higher empathy than males (mean 104.4, SD = 12.2). Conclusion: The study revealed high levels of empathy among dental students at UBA, with variations by academic year and gender. These findings underscore the importance of incorporating empathy into dental education and suggest the need for curricular adjustments to further enhance empathy-related skills. Future research should explore interventions to sustain and improve empathy levels among dental students and faculty, ultimately benefiting both patients and healthcare providers.